Personal, passionate, participatory inquiry into social justice in education - He, Ming Fang; Phillion, JoAnn (Research for social justice., 2008)
Scope of the Book: Personal~Passionate~Participatory Inquiry into Social Justice in Education, the first book in the series, features 14 programs of social justice oriented research on life in schools, families, and communities. This work, done by a diverse group of practitioner researchers, educators, and scholars, connects the personal with the political, the theoretical with the practical, and research with social and educational change. These inquiries demonstrate three distinct qualities. Each is personal, compelled by values and experiences researchers bring to the work. Each is passionate, grounded in a commitment to social justice concerns of people and places under consideration. Each is participatory, built on long-term, heart-felt engagement, and shared efforts. The principle aspect of the inquiries featured in the book series that distinguish it from others is that researchers are not detached observers, nor putatively objective recorders, but active participants in schools, families, and communities. Researchers have explicit research agendas that focus on equity, equality, and social justice. Rather than aiming solely at traditional educational research outcomes, positive social and educational change is the focal outcome of inquiry. The researchers are diverse and their inquiries are far ranging in terms of content, people and geographic locations studied. These studies reflect new and exciting ways of researching and representing experience of the disenfranchised, underrepresented, and invisible groups seldom discussed in the literature, and challenge stereotypical or deficit oriented perspectives on these groups. This book informs pre-service and in-service teachers, educators, educational researchers, administrators, and educational policy makers, particularly those who advocate for people who are marginalized and those who are committed to the enactment of social justice and positive educational and social change.